Optimization method for attribute-based cryptographic access control in mobile cloud computing - Jian LIU; Ming XIAN; Huimei WANG; Hong RONG (Tongxin xuebao)
For the problem of secure data sharing and access control in mobile cloud,the drawback of traditional cryptographic access control schemes was deeply analyzed.Considering the truth that mobile devices were usually equipped with limited resources,an optimized attribute-based cryptographic access control scheme was proposed in this study.In the proposed scheme,a third party proxy was introduced into the system model,and the two-layer encryption method was applied.Combining traditional attribute-based encryption (ABE) algorithm with multi-secret sharing and split measurement of ABE encryption,the scheme could greatly reduce the cost of mobile users in terms of data publish and access management.Theoretical and experimental analysis shows that the contribution can well meet the requirements of mobile cloud in terms of security,computational complexity and communication cost,which means that it is promising for future applications.